Supercritical carbon dioxide-mediated hydrothermal extraction of bioactive compounds from Garcinia Mangostana pericarp - Chhouk, Kimthet (Animo Repository, 2016)
Supercritical carbon dioxide in combination with hydrothermal process was used in the extraction of bioactive compounds from Garcinia mangostana pericarp. The extraction was carried out following pre-defined ranges of temperature (120-160 °C), pressure (5-15 MPa), extraction time (30-120 min), and particle size (0.3-0.9 mm), that served as parameters for determination of optimum yield. The extracts were subsequently analyzed for their total polyphenolic contents, antioxidant activity, and alpha-mangostin recovery. The multi-variable extraction process yielded several possible responses. Using response surface methodology (RSM) with central composite design (CCD), the optimal response obtained a yield of 39.9% w/w, with 22.0 gGAE/100 gextract of total polyphenolic contents, together with 73.2 μg/mL of antioxidant activity and 0.203% w/wextract recovery of alpha-mangostin. © 2015 Elsevier B.V. All rights reserved.